CEO Age and Stock Price Crash Risk - Andreou, Panayiotis C.; Louca, Christodoulos; Petrou, Andreas P. (Review of Finance, 2017)
Abstract We show that firms with younger CEOs are more likely to experience stock price crashes, including crashes caused by revelation of negative news in the form of breaks in strings of consecutive earnings increases. Such strings are accompanied by large increases in CEO compensation that do not dissipate with crashes. These findings suggest that CEOs have financial incentives to hoard bad news earlier in their career, which increases future crashes. This negative impact of CEO age effect is strongest in the presence of managerial discretion. Overall, the findings highlight the importance of CEO age for firm policies and outcomes.